Chemoselective reduction of α, β-unsaturated ketones to allylic alcohols under catalyst-free conditions. Issue 4 (20th January 2022) - Jian, Kaixia; Li, Bingnan; Zhu, Shuxian; Xuan, Qingqing; Song, Qiuling
Abstract : A strategy of chemoselective reduction of α, β-unsaturated ketones was developed in our group. H3 N·BH3 would prefer to coordinate with CO bond, forming six-membered ring, and ketones were hydrogenated via concerted double-hydrogen-transfer process. Abstract : Chemoselective reductions of α, β-unsaturated ketones to afford the corresponding allylic alcohols have always been challenging. Precious metals and ligands have always been employed in these transformations. Herein, we describe an ever more expedient, green and general method for the chemoselective reductions of exo - and endo -α, β-unsaturated cycloketones and acyclic α, β-unsaturated ketones in the presence of H3 N·BH3 under catalyst-free conditions. The polarized H3 N·BH3 preferred to coordinate with the polarized CO bond, forming a six-membered transition state, and then the reduced products were furnished via a concerted double hydrogen transfer process. This well explained the absolute chemoselectivity.